The Usability and Impact of Mobile Health Applications on Tuberculosis Treatment Regimen: A Systematic Review - Suraya, Andi Safutra; Jannah, Fitriatul; Erindia , Firnanda; Nurwahidah , Nurwahidah; Chayatush Sholichah, Ahla (Fundamental and Management Nursing Journal, 2022)
Introduction: Tuberculosis (TB) remains a major public health problem worldwide, including in Indonesia. Adherence to the therapeutic regimen is one of the indicators in TB management. However, dropout rates among those undergoing TB therapeutic regimens were found to be high. This study aims to review published articles on the usefulness of mobile health apps for adherence to TB treatment regimens and among healthcare workers. Method: This systematic review applied the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) guideline. The results were reported using a descriptive-narrative approach. The following databases: Scopus, Pubmed, and Proquest were comprehensively searched to find articles from January 1st, 2018 to June1st, 2022. Inclusion was made for English and full-text articles. Results: Fourteen (14) articles were yielded. A total of 2.408 TB sufferers and health workers use the mobile health application. Findings on the impacts of the usability of mobile health applications on the adherence of TB's treatment regimen: TB sufferers mostly use mobile health to access information about TB via Short Message Service (SMS), WhatsApp Messenger, voice or telephone calls, video-observed therapy (VOT), or a toll-free mobile health modification, namely 99DOTS. Conclusions: Mobile health applications tend to benefit people living with TB. The findings of the study emphasize the importance of mobile health applications for TB management. Mobile health apps increase patients motivation to adhere to the recommended regimen, which is one of the key TB management strategies.